2022
DOI: 10.1038/s41598-022-22234-9
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin thresholds for cardiac and liver hemosiderosis in β-thalassemia patients: a diagnostic accuracy study

Abstract: Ferritin is frequently used to screen some dire consequences of iron overload in β-thalassemia patients. The study aimed to define the best cutoff point of ferritin to screen for cardiac and liver hemosiderosis in these cases. This was a registry-based study on β-thalassemia patients living throughout Mazandaran province, Iran (n = 1959). In this diagnostic research, the index test was ferritin levels measured by a chemiluminescent immunoassay. As a reference test, T2*-weighted magnetic resonance imaging (T2*-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have consistently shown that higher ferritin levels correlate with hepatic iron concentration and are predictive of hepatic complications in thalassemia major. [ 5 6 ] Elevated serum aminotransferases, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), indicate hepatocellular injury, while declining albumin may reflect synthetic dysfunction in advanced liver disease. [ 7 ] Several researchers have reported derangements in liver enzymes and synthetic function in transfused thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently shown that higher ferritin levels correlate with hepatic iron concentration and are predictive of hepatic complications in thalassemia major. [ 5 6 ] Elevated serum aminotransferases, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), indicate hepatocellular injury, while declining albumin may reflect synthetic dysfunction in advanced liver disease. [ 7 ] Several researchers have reported derangements in liver enzymes and synthetic function in transfused thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%
“… 3 7 Most hematological societies recommend a serum ferritin (SF) level greater than 1000 ng/mL as an indication for initiation of iron chelation therapy in TDT patients. 3 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%